2001
DOI: 10.1002/app.2003
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerizaton of hyperbranched aliphatic acrylated poly(amide ester). II. Photopolymerization kinetics

Abstract: A hyperbranched aliphatic poly(amide ester) ending with hydroxyl groups based on 4-N,N-di(2-hydroxy ethyl)-4-ketobutyric acid (DKBA) and 2-ethyl-2-(hydroxymethyl)-1,3-propanediol (TMP) was modified with acryloyl chloride, resulting in a radiation-curable, hyperbranched acrylated poly(amide ester). This hyperbranched polymer was characterized with respect to ultraviolet cure rate, unsaturation conversion, and mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They are generally synthesized by repeated reactions of multifunctional monomers, mostly AB 2 type monomers. UV curable oligomers based on amine–ester, ester–amide, and ether–amide with AB 2 type monomers have been prepared by the authors 8–10. However, the UV cured films from those materials are all flammable when attacked by a fire without addition of other flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…They are generally synthesized by repeated reactions of multifunctional monomers, mostly AB 2 type monomers. UV curable oligomers based on amine–ester, ester–amide, and ether–amide with AB 2 type monomers have been prepared by the authors 8–10. However, the UV cured films from those materials are all flammable when attacked by a fire without addition of other flame retardants.…”
Section: Introductionmentioning
confidence: 99%
“…with UV intensity. Lecamp et al 34 reported that in the case of photoinitiated polymerization, the initiation rate is very high. Thus, crosslinking systems cannot be in voluminal equilibrium because volume shrinkage rate is much slower than chemical reaction rate.…”
Section: Effect Of Uv Light Intensitymentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Coatings that are abrasion resistant and require short cure time are much desired. The acrylic monomer/oligomer is an important UV-curable resin widely used for coatings because of its excellent optical properties and easy processability.…”
Section: Introductionmentioning
confidence: 99%